A home-based longitudinal study of vocalization behaviors across infants at low and elevated risk of autism. (November 2021) - DeVeney, Shari L.; Kyvelidou, Anastasia; Mather, Paris
Background and Aims: The purpose of this exploratory study was to expand existing literature on prelinguistic vocalizations by reporting results of the first home-based longitudinal study examining a wide variety of behaviors and characteristics, including early vocalizations, across infants at low and elevated risk of autism spectrum disorder (ASD). The study of vocalizations and vocalization changes across early developmental periods shows promise in reflecting early clinically significant differences across infants at low and elevated risk of ASD. Observations of early vocalizations and their differences during infancy could provide a reliable and essential component of an early developmental profile that would lower the average diagnostic age for ASD. However, studies employing observation of vocalization behaviors have been limited and often conducted in laboratory settings, reducing the external generalization of the findings. Methods: The present study was conducted to determine the consistency of previous findings with longitudinal data collected in home environments. Infants in the present study represented elevated risk from two etiological backgrounds, (a) infants born prematurely and with low birth weight and (b) infants who had an older sibling diagnosed with ASD. All data were collected in the infants' homes and compared with data collected from infants with low likelihood of ASD. The study included 44 participants (31 in the low-risk sample, 13 in the high-risk sample) with vocalization behaviors observed at 6- and 12-months through 20-min semi-structured play interactions with caregivers. Observations were video-recorded and later coded for speech and non-speech vocalizations. Results: Differences in the 6-month vocalization behaviors were not statistically significant across risk levels of ASD. By 12 months; however, risk group differences were evident in the total number of vocalizations overall with specific differences across groups representing moderate to large, clinically relevant effects. Infants at low risk of ASD demonstrated significantly greater developmental change between 6- and 12-months than did the infants at high risk. Data were also reviewed for differences across high-risk group etiologies. Conclusions: The present study was unique and innovative in a number of ways as the first home-based longitudinal study examining infant vocal behaviors across low and high risk of ASD. Many of the present study findings were consistent with previous cross-sectional investigations of infants at elevated risk for ASD, indicating support for further home-based longitudinal study in this area. Findings also indicated some preliminary subgroup differences between high-risk etiologies of ASD. Vocalization differences across high risk groups had not been previously addressed in the literature. Implications: Vocalization differences are notable by 12-months of age between infants at low and elevated risk of ASD and infants at high risk demonstrated reduced developmental changes between 6- and 12-months compared to the infants at low risk. Observation of early infant vocalization behaviors may reasonably occur in the home, providing early childhood professionals and researchers with empirical support for data collection of child-caregiver interactions in this setting. Potential differences across high-risk etiologies warrant further investigation.